2015
DOI: 10.3844/ojbsci.2015.178.184
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Prevalence of Cardiovascular Risk Factors in an Iranian Urban Population

Abstract: In Iran, more than 40% of mortality is a result of cardiovascular disorders. The aim of this study was compare of cardiovascular risk factors in urban men and women. This cross-sectional analytic study was performed in urban population of Jahrom in 2008-2009. Subjects aged 30 years or older were selected by multi stage random sampling. Serum lipids including total cholesterol, triglyceride, HDL and LDL cholesterol and also fasting blood sugar were measured. Their blood pressure was measured under standard meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
9
1
Order By: Relevance
“…[ 2 ] Another study focused on OB prevalence among male and female aged 30 years and showed above as 9.9% and 24.8% for, respectively. [ 3 ] OB is the main public health problem that is connected with extensive morbidity and mortality. [ 4 5 ] A number of investigators believe that OB increased risk of making a variety of diseases, such as prediabetes, Type 2 diabetes mellitus, prehypertension, cardiovascular disease, gastrointestinal disease, nonalcoholic fatty liver disease, and certain cancers.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Another study focused on OB prevalence among male and female aged 30 years and showed above as 9.9% and 24.8% for, respectively. [ 3 ] OB is the main public health problem that is connected with extensive morbidity and mortality. [ 4 5 ] A number of investigators believe that OB increased risk of making a variety of diseases, such as prediabetes, Type 2 diabetes mellitus, prehypertension, cardiovascular disease, gastrointestinal disease, nonalcoholic fatty liver disease, and certain cancers.…”
Section: Introductionmentioning
confidence: 99%
“…According to a study by Fallahzadeh and associates on estimating the prevalence and trends of obesity in the Iranian population, it was reported that 16.5% of Iranian subjects older than 18 years were obese (5). Furthermore, as part of the Jahrom Health Study (JHS), 24.8% of women aged 30 years and above were obese (6). In obese women, it has been reported that a small decline in muscle strength may cause di culties in bearing their excess weight and in moving e ciently (7).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of obesity is increasing worldwide1 and it was reported in 2011–2013 that 16.5% of Iranian subjects older than 18 years were obese 2. Also, as part of the Jahrom Health Study (JHS), 9.9% of men and 24.8% of women aged 30 years or older were obese 3. Obesity is a strong risk factor for several chronic diseases, such as hypertension (HTN), pre-diabetes, diabetes mellitus type 2 (DMT2), dyslipidaemia and cardiovascular disease 49.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a strong risk factor for several chronic diseases, such as hypertension (HTN), pre-diabetes, diabetes mellitus type 2 (DMT2), dyslipidaemia and cardiovascular disease 49. According to a study conducted in Jahrom, the prevalence of cardiovascular risk factors in adults were 11.6% for diabetes mellitus,10 31.4% for hypertension,5 19.8% in men and 16.2% in women for hypertriglyceridemia3 and 9.4% in men and 13.3% in women for hypercholesterolemia 3…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation